The Influence of the Korean Wave and Advertising Tagline on the Purchase Decision of Lemonilo Spicy Korean Daebak Flavor in Malang and Surrounding Areas - Hellyani, Catharina Aprilia; Basory, Hartomy Akbar; Bilqis, Syadzalina (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the effect of Korean wave, and taglines on purchasing decisions for Korean spicy lemonilo noodles. The Korean wave triggers public interest in buying these products, which has an impact on purchasing decisions. The Korean Spicy Lemonilo Noodle product also uses a Tagline strategy in its product advertisements which has the hastag #PedasnyaDaebak. This study aims to analyze the influence of Korean wave and tagline on purchasing decisions for Lemonilo Spicy Korean Taste Spicy Daebak in Malang and its surroundings. The research was conducted on respondents who had bought and consumed Korean spicy lemonilo noodles as many as 272 respondents. This study uses primary data and data collection is done by survey via Google Form. The type of research used is quantitative and explanatory research methods. The results of this study indicate that Korean Wave and Tagline have a simultaneous positive influence on purchasing decisions for Korean Spicy Lemonilo in Malang and surrounding areas.